2009
DOI: 10.3109/01676830903104728
|View full text |Cite
|
Sign up to set email alerts
|

Dysthyroid optic neuropathy: atypical initial presentation and persistent visual loss

Abstract: DON prognosis is highly variable. Our results suggest that a non-inflammatory element, probably vascular could be involved in atypical DONs. An earlier recognition could prompt to rapid surgical treatment for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
1
11
0
1
Order By: Relevance
“…Patients with DON are older compared to patients with GO but without DON [12]. The average age of patients with DON is about 55 years [15,23,24], which is similar to our results. An older age may be associated with adverse factors related to reconstruction in the muscles, which may affect the therapeutic efficacy.…”
Section: Discussionsupporting
confidence: 90%
“…Patients with DON are older compared to patients with GO but without DON [12]. The average age of patients with DON is about 55 years [15,23,24], which is similar to our results. An older age may be associated with adverse factors related to reconstruction in the muscles, which may affect the therapeutic efficacy.…”
Section: Discussionsupporting
confidence: 90%
“…In another large retrospective study, 8.6% of patients with TED developed DON, and patients with DON were older (54 years versus 46 years)) compared to those without DON[1]. Several other studies also show a strong correlation between age and DON [17,18]. For every decade increase in age of onset of TED, the odds of developing DON may increase by 58%[11].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Age may also affect the response to DON treatment with younger age predicting a better outcome (p=0.049)[19]. Male gender also shows a strong correlation with the development of DON, especially with advancing age[1,4,5,17]. …”
Section: Risk Factorsmentioning
confidence: 99%
“…It is suggested that vascular ischaemia might be involved in the cases with DON. 8 If the response to pulse therapy is poor after a 1-2week period, prompt orbital decompression should be performed. 4,5 The prognosis for DON is highly variable, and to date, no studies have analysed the relationship between the state of thyroid function and the outcome of pulse therapy.…”
Section: Discussionmentioning
confidence: 99%